PENGELOLAAN OBJEK WISATA BERBASIS MASYARAKAT LOKAL DI SIWANG PARADISE NEGERI URIMESSING KOTA AMBON - Ayunda Safitri; Th. M. Silaya; Lesly. Latupapua (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2022)
This research was conducted with the aim of knowing how to manage local community-based tourism objects and the constraints in managing tourist objects in Siwang Paradise. In this study, qualitative methods were used in data collection, namely by distributing questionnaires to the community around the Siwang Paradise tourist attraction. the data from the results of the distribution of the questionnaires were processed by descriptive statistical methods which then processed the distribution of the questionnaires to be processed into data in the form of tables and explanations. The results obtained are that the management of the Siwang Paradise tourist attraction is only carried out by community groups who still have family relationships and also involve local youth. In the implementation of the management of the tourism object, it also involves local people who are paid by the manager. The obstacle in managing the Siwang Paradise tourist attraction is the absence of assistance or involvement from the Ambon City government. This can be seen from the condition of the road to the Siwang Paradise tourist attraction that has not been asphalted, the parking area is inadequate, the toilets are still in a simple form and the need for clean water is still inadequate. And the lack of participation from the surrounding community.